Media LASERIN dalam Meningkatkan Hasil Belajar Sejarah Penjajahan Belanda Di Indonesia - Khoirulina, Lilis (Universitas Nusantara PGRI Kediri, 2018)
IPS learning in primary schools has several problems, among them the use of media and methods that are still conventional and tend to be monotonous, convey the material by using lecture method, then give the task. Students are not directly involved in the learning process and tend to just sit, be quiet, listen, be less active, have less attention to the material presented by the teacher, are reluctant to ask the teacher even though they do not understand the taught material and less enjoyable learning atmosphere, the lessons learned by the students are low because the subject matter is not fully mastered by the students. The use of LASERIN media on the subject of Dutch Colonial History in Indonesia to the Grade V Students of SDN Dermo I Kota Kediri Lesson 2014/2015 apply active, creative, effective and fun learning (PAKEM) which stimulates active students and is directly involved in learning activities and is motivated by itself to learn because they feel happy and find the material by understanding LASERIN poetry and can understand the demands of learning history materials. Student learning outcomes using LASERIN media are increasing. Assessment of learning outcomes at the second meeting amounted to 63.83% and the fourth meeting increased again to 89.37%. The above results show the need for media / tools that help learners to capture the message or purpose of the learning process.